Workshop Penyegaran Materi Ajar Matematika Sekolah Dasar dengan Penggunaan Software Algebrator pada Smartphone - Iyan Rosita Dewi Nur; Dani Firmansyah; Vara Nina Yulian (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
One of the problems encountered by teachers in learning mathematics is that many students have difficulty solving multiplication problems, including multiplication of fractions. In addition, the teachers also admitted that they experienced many difficulties in teaching multiplication material, especially multiplication of fractions. The main objective in implementing this activity is to improve the ability of teachers in mastering mathematics teaching materials by utilizing the role of technology in learning mathematics by using Algebrator Software which in the end is expected to increase students' abilities and interest in learning mathematics. This activity was carried out in the form of a workshop with material on algebrator software. This activity involved 25 participants who are teachers at the al Firdaus Gintungkerta foundation in Karawang Regency. From the independent assignments given to the participants, around 90% of the activity participants were able to smoothly solve problems using the Algebrator software application on their smartphone. The response of the workshop participants to the material provided was very good, as seen from the enthusiasm of the participants in asking questions or problems and responding or providing responses when given questions or problems. Mentoring is carried out once after 3 weeks of the workshop activities being completed.Keywords: Workshop, Elementary School Mathematics, Software Algebrator ABSTRAKPermasalahan yang ditemui oleh para guru dalam pembelajaran matematika ini salah satunya adalah banyak siswa yang menemui kesulitan dalam menyelesaikan soal-soal perkalian, termasuk perkalian pecahan. Selain itu, para guru juga mengaku merasakan banyak menemui kesulitan dalam mengajarkan materi perkalian terutama perkalian pada pecahan. Tujuan Utama dalam pelaksanaan kegiatan ini yaitu untuk meningkatkan kemampuan para guru dalam penguasaan materi ajar matematika dengan memanfaatkan peran teknologi dalam pembelajaran matematika dengan menggunakan Software Algebrator  yang mana pada akhirnya diharapkan dapat meningkatkan kemampuan serta minat siswa dalam belajar matematika. Kegiatan ini dilaksanakan dalam bentuk workshop dengan materi tentang software algebrator. Kegiatan ini melibatkan 25 peserta yang merupakan guru di yayasan al Firdaus Gintungkerta yang berada di Kabupaten Karawang. Dari pemberian tugas mandiri yang diberikan kepada peserta, sekitar 90% peserta kegiatan dengan lancar dapat menyelesaikan soal dengan menggunakan aplikasi software Algebrator di smartphone. Respon para peserta workshop terhadap materi yang diberikan sangat baik, terlihat dari antusiasme para peserta dalam mengajukan pertanyaan atau permasalahan serta menanggapi atau memberikan tanggapan saat diberikan pertanyaan atau permasalahan. Pendampingan dilakukan sekali setelah 3 minggu kegiatan workshop selesai dilaksanakan. Kata Kunci: Workshop, Matematika Sekolah Dasar, Software Algebrator